THE EFFECT OF BRAND TRUST AND PRODUCT DESIGN ON INTEREST IN BUYING NMAX MOTORCYCLES - Eko Putra; Mega Usvita; Elondri Elondri (Ikatan Dosen Menulis, 2026)
This study aims to determine (1) the effect of brand trust on the intention to purchase an NMAX motorbike; (2) the effect of product design on the intention to purchase an NMAX motorbike; and (3) the combined effect of brand trust and product design on the intention to purchase an NMAX motorbike in Kinali Sub-district. The population comprised all residents of Kinali Sub-district who intended to purchase an NMAX motorbike, with a sample size of 74 respondents. The sampling method used in this study was non-probability sampling, specifically accidental sampling, which is a technique of determining the sample based on chance; that is, residents of Kinali Sub-district who happened to encounter the researcher by chance could be used as a sample, provided that the person encountered was deemed suitable as a data source. Variables were measured using a Likert scale; this study is classified as quantitative research. It was found that the Brand Trust variable has a positive and significant effect on the intention to purchase an NMAX motorbike, with a regression coefficient of 0.658 and a significance level of 0.000 (<0.05). The Product Design variable has a positive and significant effect on the purchase intention for the NMAX motorbike in Kinali sub-district, with a regression coefficient of 0.484 and a significance value of 0.000 (<0.05). The independent variables collectively have a positive and significant effect on the purchase intention for the NMAX motorbike in Kinali sub-district, with a regression coefficient of 104.963 and a significance value of 0.000 (<0.05). The coefficient of determination is 75 per cent. The remaining 25 per cent is influenced by other variables not included in this analysis.